Integral Formulae of Bernoulli and Genocchi Polynomials - Seog-Hoon Rim; Joung-Hee Jin; Joohee Jeong (International Journal of Mathematics and Mathematical Sciences)
Recently, some interesting and new identities are introduced in the work of Kim et al. (2012). From these identities, we derive some new and interesting integral formulae for Bernoulli and Genocchi polynomials.